Character strengths as protective factors against engagement in sexting in adolescence - Yépez-Tito, Paula; Ferragut, Marta; Blanca, Maria J. (Anales de Psicología / Annals of Psychology, 2021)
Sexting is a new kind of sexual interaction among adolescents that has been linked to both psychological problems and sexual risk behaviors. Although studies have examined the relationship between sexting and personality traits, its possible association with character strengths remains unexplored. The aim of this study was to analyze which character strengths may function as protective factors against engagement in sexting, controlling for other variables that might influence this relationship. Adolescents completed questionnaires about technological resources, active sexting, and character strengths. The results from hierarchical regression showed that active sexting was positively related to the strengths of curiosity and humor and negatively related to fairness and authenticity. These findings suggest that school- or family-based programs aimed at preventing sexting should include specific activities that encourage a positive use of curiosity and humor and which seek to promote honesty, respect, fairness, and responsibility in the use of technology for interpersonal relationships